Research on Noise Reduction Scheme of Heat Pump Unit in a Square - Xueyong Zhang; Yuanyuan Hu; Shengyuan Geng; Qianyong Hu; Huanbao Wang (Journal of Chemistry)
Heat pump unit is a host device located in the central air-conditioning terminal, providing cold and hot water. Heat pump unit has the advantages of energy saving, environmental protection, easy maintenance, and so on. It is adopted to solve the problems of refrigeration and heating in ventilation and air conditioning from many engineering projects in China. When the equipment is turned on, however, the high noise generated by the heat pump unit has a very negative impact on the life and work of the surrounding residents. Therefore, noise reduction is needed to improve the environment quality. In this paper, the noise of the air-cooled heat pump unit of the square area in Shanghai was detected, the noise source was analyzed, and the corresponding noise reduction scheme was proposed. After the completion of the scheme, measurements indicate that A-weighted sound pressure level is less than or equal to 60 dB (A) during the day and less than or equal to 50 dB (A) at night, which meets the relevant national noise limit emission standards and conforms to the second-class quality standard of the acoustic environment.